Akurasi dan Ketepatan Pengkodean Diagnosis pada Kasus Obstetric di RST Dr. Asmir DKT Salatiga - Kumala Dewi, Ratih; Evita Aurilia Nardina; Ferdiansyah Hari Nugroho (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2024)
Accurate and precise diagnosis coding in obstetric cases at Dr. Asmir DKT Hospital, Salatiga, is crucial for effective medical record management. This study utilized an analytical quantitative approach with a cross-sectional method to explore the relationship between the accuracy and precision of diagnosis coding. The sample comprised 100 obstetric cases selected from inpatients during the first quarter (January – March 2024). Data analysis revealed that 68% of the 72 analyzed cases had accurate diagnosis coding, while 32% were inaccurate. Similarly, 71% of the cases were coded precisely, with 29% coded imprecisely. Chi-Square analysis indicated a significant relationship between accuracy and precision of diagnosis coding (p = 0.002). Factors influencing inaccuracies and imprecisions in coding included legibility of physician notes in medical records, inadequate understanding of the coding system (ICD-10), and completeness of medical documentation. To enhance coding quality, regular training for healthcare staff is recommended, alongside strengthening internal audit systems and developing more efficient medical record information systems.